PENGARUH SUMBER PENDAPATAN ASLI DAERAH (PAD) TERHADAP DANA ALOKASI UMUM (DAU) PADA PEMERINTAHAN KOTA MEDAN - Sri Rahayu (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
General Alocation Funds (DAU) is the amount of funds allocated to each autonomous regins (Province/District/City) in Indonesia each year as development funds. General Alocation Funds and various forms of transfers from Government Center should only be a supplement for the implementation of government and regional development. Seen from DAU in Government of Medan in 2008 - 2015 shows that DAU which comes from Government Center each year continues to show improvement. The purpose of this research is to find out how much the influence of Local Taxes, Local Retributions, Profit Part of BUMD, and Other Legal PAD to DAU in Government of Medan. This research conducted in Government of Medan by using secondary data and quantitative sourced from Actual Receipt Municipality Government of Medan in 2008 - 2015 obtained from Badan Pusat Statistik Kota Medan. With limited data, this study used quarterly data through interpolation of annual data by using EViews. The analyzing data method used statistic method with SPSS. The result of the research with simultaneous test showed that Local Taxes, Local Retributions, Profit Part of BUMD, and Other Legal PAD affect DAU. The result of partial test showed that Local Taxes and Other Legal PAD affect DAU significantly but Local Retributions and Profit Part of BUMD did not. Amounted to 59,1% change in DAU can be explained by four independent variables and the rest 40,9% explained by another factors that not included in this research.Key Words: Local Taxes, Local Retributions, Profit Part of BUMD, Other Legal PAD, and General Alocation Fund (DAU).